Acute beetroot juice supplementation does not improve cycling performance in normoxia or moderate hypoxia - MacLeod, K. E.; Nugent, S. F.; Barr, S. I.; Koehle, M. S.; Sporer, B. C.; MacInnis, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
Beetroot juice (BR) has been shown to lower the oxygen cost of exercise in normoxia and may have similar effects in hypoxia. We investigated the effect of BR on steady-state exercise economy and 10-km time trial (TT) performance in normoxia and moderate hypoxia (simulated altitude: ~2500 m). Eleven trained male cyclists (VO2peak = 60 ml·kg-1·min-1) completed four exercise trials. Two hours before exercise, subjects consumed 70 mL BR (~6 mmol nitrate) or placebo (nitrate-depleted BR) in a randomized, double-blind manner. Subjects then completed a 15-min self-selected cycling warm-up, a 15-min steady-state exercise bout at 50% maximum power output, and a 10-km time trial (TT) in either normoxia or hypoxia. Environmental conditions were randomized and single-blind. BR supplementation increased plasma nitrate concentration and fraction of exhaled nitric oxide relative to PL (p < .05 for both comparisons). Economy at 50% power output was similar in hypoxic and normoxic conditions (p > .05), but mean power output was greater in the normoxic TT relative to the hypoxic TT (p < .05). BR did not affect economy, steady-state SpO2, mean power output, or 10-km TT completion time relative to placebo in either normoxia or hypoxia (p > .05 in all comparisons). In conclusion, BR did not lower the oxygen cost of steady-state exercise or improve exercise performance in normoxia or hypoxia in a small sample of well-trained male cyclists.